The prevalence of depression and anxiety in gastrointestinal out-patients of tertiary general hospitals in Beijing - Jiang, Rong-huan; Yu, Xin; Ma, Hong; He, Yan-ling; Wei, Jing; Bai, Wen-pei; Liu, Mei-yan (Chung-hua nei kʿo tsa chih, 2009)
To explore the prevalence and physician's recognition of depression and anxiety disorder in gastrointestinal out-patients of three tertiary general hospitals in Beijing. A hospital-based cross-sectional survey was conducted in the gastrointestinal out-patient departments of three tertiary general hospitals in Beijing from May to June 2007. Total 517 subjects were recruited consecutively within a one month period. All the subjects were screened with Hospital Anxiety Depression Scale (HADS). The subjects with HADS score of 8 and over were interviewed and diagnosed by psychiatrists using Mini International Neuropsychiatric Interview (MINI). The physicians made the diagnosis and management without knowing the results of MINI and HADS score. Among the 517 cases, 301 had a HADS score of 8 and above and 244 were interviewed by psychiatrists; the response rate was 81.1%. The prevalence according to Diagnostic and Statistical Manual of Mental Disorders Fourth edition of depressive disorders and anxiety disorders in ga